(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2023)
This article delves into the unique challenges that introverts face in the realm of public speaking and offers strategies to harness their strengths and excel on stage. It recognizes that introverts bring valuable qualities to public speaking, such as deep knowledge, empathy, and introspection, which can captivate audiences. By exploring the specific tools and techniques that introverts can employ to overcome anxiety, boost confidence, and deliver compelling speeches, this study aims to empower introverted individuals to embrace public speaking and realize their full potential as effective communicators.